SPE Western Regional Meeting 2005
DOI: 10.2118/93874-ms
|View full text |Cite
|
Sign up to set email alerts
|

Problem of Monitoring of Arbitrary Oriented Trajectories of Boreholes with Small Diameters by Means of Strapdown Gyroscopic Inclinometers and its Solution Methods

Abstract: The possibility to use two-axis gyro rate sensor (GRS) in principle for measurement of trajectory parameters is shown., in the present report. The angular momentum vector of this sensor is oriented along the longitudinal axis of the borehole device. The errors and limits of this scheme utilization are defined, when operating in gyrocompassing mode. A method of utilization of the scheme with a longitudial gyro is original for two operation modes (gyrocompassing and analytical directional gyro) near the line Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But the aforesaid method used for the borehole azimuth determination is not a unique one. Earlier the authors have shown [1] that it is possible to calculate the azimuth value using only the first expression from (7), i.e. to calculate the desired angle with the help of arcsin function, namely:…”
Section: Azimuth Determination Algorithms In An "Axial" Schemementioning
confidence: 99%
See 1 more Smart Citation
“…But the aforesaid method used for the borehole azimuth determination is not a unique one. Earlier the authors have shown [1] that it is possible to calculate the azimuth value using only the first expression from (7), i.e. to calculate the desired angle with the help of arcsin function, namely:…”
Section: Azimuth Determination Algorithms In An "Axial" Schemementioning
confidence: 99%
“…Such statement of the problem was not considered earlier, probably, due to seeming evidence of the conventional algorithm, in which arctg function is used. It was shown in the authors' paper [1] that there exists another azimuth calculation algorithm with the use of arcsin function. In this case the properties of the desired angle are changing: in particular, the limitation area for the use of "axial" scheme is substantially narrowed down, i.e.…”
Section: Introductionmentioning
confidence: 99%